Antifungal Activity of Essential Oil Isolated from Pelargonium roseum against Grey Mould (Botrytis cinerea) of Cherry Tomato - Fuyan LIU; Runxia YANG; Yangcuiji ZHENG; Chongjun ZHAO; Liming FAN; Fawu SU; Min YE (Shipin gongye ke-ji)
To investigate the chemical composition of Pelargonium roseum essential oil (EO) and its antifungal activities against Botrytis cinerea of cherry tomato as a potential alternative to synthetic chemical fungicides for postharvest preservation of fruits and vegetables. In this study, the EO of P. roseum was extracted by water vapor distillation, and the chemical components were determined by gas chromatography-mass spectrometry (GC-MS). The inhibitory effects of different concentrations of the EO and its compounds on the growth of mycelium and the germination of spores were determined by the poison food technique and dual culture method, respectively. Results showed that the extraction rate of P. roseum EO was 0.43%, and 19 compounds were identified in the EO. The major constituent was citronellol (52.16%) followed by nerol (21.93%), citronellyl formate (9.87%), and isomenthol (5.18%). And the EO and its compounds had a significant inhibitory effect (P<0.05) on growth of mycelium and germination of spores against B. cinerea. The inhibitory activity of the dual culture method was much better than that of the poison food technique. There was a dosage-effect relationship between the dosage of the EO and inhibitory activity. In vivo vapor contact test results showed that the EO of P. roseum and its compounds had good inhibitory activity against the postharvest grey mould of cherry tomatoes, and the disease control rate was as high as 98.45% when the dosage of EO was 250.00 mg/L. Thus, the results obtained in this study demonstrate the potential of the EO from P. roseum as an eco-friendly natural fungicide using for postharvest disease control, but its mechanism of action needs to be further investigated.